Spencer Phips, Esq ; lieutenant-governor and commander in chief ... To [blank] Greeting : Whereas notwithstanding the repeated orders issued to the several colonels in the province, there is a deficiency in the whole number of men ordered to be raised for the service of the Crown Point expedition ... Given under my hand and seal at Boston, the eighth day of July, one thousand seven hundred and fifty-six . ([Printed by John Draper], 1756)
Ordering the militia colonels to comply with Governor Shirley's order of April 15th regarding troop quotas.